Erythropoietin Increases GABAA Currents in Human Cortex from TLE Patients. (15th July 2020) - Roseti, Cristina; Cifelli, Pierangelo; Ruffolo, Gabriele; Barbieri, Elena; Guescini, Michele; Esposito, Vincenzo; Di Gennaro, Giancarlo; Limatola, Cristina; Giovannelli, Aldo; Aronica, Eleonora; Palma, Eleonora
Abstract: Erythropoietin (EPO) is a hematopoietic growth factor that has an important role in the erythropoiesis. EPO and its receptor (EPO-R) are expressed all over in the mammalian brain. Furthermore, it has been reported that EPO may exert neuroprotective effect in animal models of brain disorders as ischemia and epilepsy. Here, we investigate whether EPO could modulate the GABA-evoked currents (IGABA ) in both human epileptic and non-epileptic control brain tissues. Therefore, we transplanted in Xenopus oocytes cell membranes obtained from autoptic and surgical brain tissues (cortex) of seven temporal lope epilepsy (TLE) patients and of five control patients. Two microelectrodes voltage-clamp technique has been used to record IGABA . Moreover, qRT-PCR assay was performed in the same human tissues to quantify the relative gene expression levels of EPO/EPO-R. To further confirm experiments in oocytes, we performed additional experiments using patch-clamp recording in slices obtained from rat cerebellum. We show that exposure to EPO significantly increased the amplitude of the IGABA in all the patients analyzed. No differences in the expression of EPO and EPO-R in both TLE and control patients have been found. Notably, the increase of IGABA has been recorded also in rat cerebellar slices. Our findings show a new modulatory action of EPO on GABAA receptors (GABAA -Rs). This effect could be relevant to balance the GABAergic dysfunction in human TLE. This article is part of a Special Issue entitled: Honoring Ricardo Miledi - outstanding neuroscientist of XX-XXI centuries . Highlights: We found an increase of GABA current amplitude in human epileptic tissue after exposition to EPO. The effect of EPO was present also in human control non-epileptic tissue. The effect was not dependent by an increase of EPO or EPO-R mRNA expression. This result was also confirmed in cerebellar rat slices. We show a new modulatory action of EPO on GABAA -Rs that could balance the GABAergic dysfunction in human TLE.